Rebranding MSMEs' Sambal Cumi Asin by BUMDesa Rasau Jaya Satu to Enhance Brand Awareness - Nur Khairani, Zhafarina; Putri, Adinda; Fitri Susilawati, Annisa; Galuh Pramesti, Ventina; Aulia Maisa, Dinda (Yayasan Ahmar Cendekia Indonesia, 2024)
Rasau Jaya Satu Village, located in Kubu Raya Regency, has a Village-Owned Enterprise (BUMDesa) with the potential to serve as a model for regional economic growth. This potential is demonstrated by its achievement of 5th place among advanced villages in Kubu Raya. However, the partner Micro, Small, and Medium Enterprises (MSMEs) under the guidance of BUMDesa Satu Hati still face challenges in business development, particularly in expanding their product reach. The KKM-PKM Management program of UNTAN was implemented to enhance business management skills, enabling the MSMEs to broaden their market. The program activities were conducted using a hands-on approach, involving direct discussions between BUMDesa, MSME owners, and the KKM-PKM team. The KKM activities were successfully executed, with the KKM team and BUMDesa Satu Hati collaborating to achieve the development of effective marketing approaches through product design and packaging innovations aimed at increasing product appeal and brand awareness among consumers.